2020
DOI: 10.21203/rs.3.rs-52315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uterotonic Effects of Aqueous and Methanolic Extracts of Lannea Acida in Wistar Rats: An in Vitro Study.

Abstract: Background: Lannea acida (Anacardiaceae), commonly called Kikié in the Noun division (West-Cameroon), is a tree whose bark is used locally to solve difficult childbirth. This study aimed to evaluate the in vitro uterotonic effects of aqueous and methanolic extracts of L. acida in female Wistar rats. Uterine strips isolated from female rats pretreated (48h) with oestradiol (5μg) were mounted in a single-organ bath containing a well aerated and thermostated De Jalon solution (37°C). The effects of L. acida extra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…Studies have shown that the expression of oxytocin receptor increases significantly with the increase of dysmenorrhea. [39] After stimulation with oxytocin, the contractile tension of uterine smooth muscle increased significantly (p < 0.05, p < 0.01), which was consistent with that reported in the literature, [40] suggesting that oxytocin can induce strong contraction similar to dysmenorrhea. Further studies showed that CW extract could significantly inhibit oxytocin-induced uterine spasm in vitro, and significantly reduce the contraction amplitude, frequency, and activity of uterine smooth muscle.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that the expression of oxytocin receptor increases significantly with the increase of dysmenorrhea. [39] After stimulation with oxytocin, the contractile tension of uterine smooth muscle increased significantly (p < 0.05, p < 0.01), which was consistent with that reported in the literature, [40] suggesting that oxytocin can induce strong contraction similar to dysmenorrhea. Further studies showed that CW extract could significantly inhibit oxytocin-induced uterine spasm in vitro, and significantly reduce the contraction amplitude, frequency, and activity of uterine smooth muscle.…”
Section: Discussionsupporting
confidence: 89%
“…Rich (Anacardiaceae) is distributed in Africa and used to treat various ailments including musculoskeletal disorders and gynaecological complains [17,18], to enhance fertility and facilitate parturition [19]. In vitro, the aqueous and methanolic extracts of stem bark induced uterotonic effects through oxytocin receptors [19]. Chronic, non-resolving inflammation is detrimental to fracture healing [20].…”
Section: Introductionmentioning
confidence: 99%